Nutritional Status in Breastfed 18-Month Old Toddlers: Cross-Sectional Findings. (29th May 2020) - Montgomery, Sarah; Ho, Gloria; Rossen, Larissa; Zibrik, Deborah; Dyer, Roger; Oberlander, Tim; Lamers, Yvonne
Abstract: Objectives: Adequate nutrition is critical for infant and toddler growth and development. Breastfeeding is recommended until 2 years of age or beyond, and breastmilk is an important source of energy and nutrients for many toddlers beyond 12 mo of age. The composition of breastmilk changes over time during the lactation period. It is not yet known how prolonged breastfeeding influences nutritional status in toddlers aged 12–24 mo. The objective of this research was to explore biomarker differences between breastfed and non-breastfed toddlers residing in Metro Vancouver, Canada. Methods: We studied cross-sectional baseline data from 18 mo old toddlers enrolled in a partially randomized controlled trial. Toddlers were categorized as breastfed (currently receiving breastmilk as the primary milk source, i.e., ≥2 times/day) and non-/occasionally-breastfed. Results: Sixty-five toddlers, with preliminary data available at the time of analysis, had an equal distribution of males and females, 68% were the first-born child, and 55%, 19%, and 26% were of European, Chinese or other ethnicity, respectively. Twenty-eight of the 18-mo old toddlers (43%) were still breastfed, with 93% ( n  = 26) receiving breastmilk as the primary source of milk. Plasma vitamin A was lower, and plasma betaine and docosahexaenoic acid (DHA) as a percentage of red blood cell fatty acids were significantly higher in breastfed toddlers compared to the other group (all P  < 0.05; Mann-Whitney U test). There was a trend for lower plasma ferritin in breastfed toddlers ( P  < 0.1). Plasma lutein, vitamin D, and choline concentrations did not differ between groups. Conclusions: These preliminary findings reflect possible differences in biomarker status between breastfed and non-/occasionally-breastfed toddlers. The analysis of total dietary intake and complementary feeding patterns is warranted to determine what types of food and beverages take the place of breastmilk in 18 mo old toddlers, and which dietary sources may explain the differing nutrient status. Funding Sources: This study is supported by The University of British Columbia, and the British Columbia Children's Hospital Research Institute, Canada, and is funded by Société des Produits Nestlé S.A.